Cracking characteristics evaluation for reinforcement basalt fiber reactive powder concrete beam using acoustic emission - Lyu, Xiang; Li, Wenjun; Hu, Hang; Ding, Xuezheng; Hu, Xiaochuan (Frontiers in Materials, 2024)
New types of fibers such as basalt fibers are gradually being used to reinforce cement-based concrete materials. To provide a basis for the further popularization of basalt fibers and basalt fiber reinforced reactive powder concrete (BFRPC) materials, the bending mechanical properties and fracture properties of BFRPC beams were investigated by innovatively applying four-point bending test and multiple acoustic parameter analysis methods. On the one hand, the load vs. displacement curve and crack pattern of reinforcement BFRPC beam were obtained from the four-point bending test. On the other hand, Acoustic emission (AE) technology was used to monitor the cracking process of reinforcement BFRPC beam under four-point bending load, and the AE signal was analyzed to illustrate the cracking characteristics of reinforcement BFRPC beam. The results revealed that AE hits, amplitude, counts, duration, and energy have a similar changing trend with bending load. Cumulative hits and cumulative energy are positively linearly related to the displacement and quadratically related to the sum of crack widths, and the correlation coefficients are all above 0.95. Besides, the cracking process of reinforcement BFRPC beam can be divided into four stages by the variation of AE basic parameters with bending load. The main rebars yielding is an important turning point of the crack characteristic of reinforcement BFRPC beam. AE signal data varies greatly in different locations, and it has an obvious advantage to detect the formation of invisible cracks. The results of predicting concrete damage and cracking by AE signal data are consistent with the experimental phenomenon. The low-stress brittle fracture caused by tensile fracture was reduced, and the tensile resistance and flexural bearing capacity of the reinforcement BFRPC beam were increased. The results obtained in this paper support the damage assessment and structural health monitoring for cement base concrete materials under bending load.